SACRED SOUNDSCAPES AND RELIGIOUS PEDAGOGY: REFRAMING CHURCH MUSIC AS A FOUNDATION FOR MUSIC EDUCATION AND PRACTICE IN NIGERIA - Dora Ifeanyi, Okunbor (African Journal of Social and Behavioural Sciences, 2026)
This article discusses church music as having played a major role in giving members opportunities to come in contact with music thereby laying a foundation for formal music education. It therefore reconceptualized church music in Nigeria as a religious pedagogical system (RPS) and not just a liturgical devotional and aesthetic practice. Forty articles were selected and analyzed. This analysis combines literature on Nigerian church music, gospel music, Pentecostal worship, hymnody, inculturation, decolonial music education, choir training, informal learning and religious education. It creates the Sacred Soundscape Pedagogy Model, which outlines the five interrelated ways in which church music impacts music education, namely, liturgical participation, informal apprenticeship, doctrinal-musical memory, cultural translation and performative formation. The article argues that the churches in Nigeria function as informal conservatoires where singers, instrumentalists, conductors, composers and worship leaders are trained through the process of participation, imitation, repetition, correction and public performance. Alongside this, it also reveals that there are tensions related to the teaching of church music: the dominance of Western music, the lack of a robust curriculum framework, commercialisation, lack of theological depth, generational gap and lack of documentation of indigenous Christian sound. The article makes a contribution to the fields of music education, African Christianity, religious pedagogy and ethnomusicology by suggesting that the future of Nigerian music education cannot be oblivious to the sacred soundscapes in which many musicians are first exposed to music, learn their craft, and imagine music. It concludes from the articles analyzed that Nigerian church music historically and presently serves as a significant musical learning ground, religious formation, cultural negotiation and professional practice.